Ethnomathematics and the primary school pupils’ achievement in mathematics in Ogbia Local Government Area, Bayelsa State, Nigeria - Eze, Foluke Bosede (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
This study investigated the effect of the ethnomathematics approach on pupils' achievement in mathematics (plane shapes) in the Ogbia Local government area of Bayelsa State, Nigeria. One research question and one null hypothesis guided the study. The study employed the pretest-posttest nonequivalent control group design on a sample size of seventy-four (74) pupils in two primary schools randomly sampled from the sixty-two (62) primary schools in the LGA. The researcher constructed an instrument titled EthnoMathematics Test (EMT) with ten (10) multiple-choice items validated by two (2) Mathematics Educators and one (1) lecturer in Measurement and Evaluation from the Federal University, Otuoke, Bayelsa State. The EMT was trial tested on thirty (30) pupils who were not part of the study; the responses from the trial testing were used to determine the internal consistency of the items using Kuder- Richardson Formula 20 (KR20), and the reliability coefficient obtained is 0.78. The test items were first distributed to the subjects to determine the initial differences between the respondents, after which the two groups of subjects were treated with the ethnomathematics and the traditional methods, respectively. After the experiment, the test items were distributed to the subjects after the reshuffling of the items. The responses were analyzed using mean and standard deviation to answer the research question, while t-test statistics were used to test the hypothesis at alpha level ≤ 0.05. The results revealed, among others, that the ethnomathematics approach was more effective in facilitating pupils' achievement in plane shapes. The finding had severe implications for mathematics teachers and stakeholders in mathematics education. Therefore, it was recommended, amongst others, that teachers should endeavour to teach mathematics by incorporating elements of culture (songs, food, language, tools, and equipment) of the environment so that the pupils can comprehend.